2019
DOI: 10.1111/jfb.14083
|View full text |Cite
|
Sign up to set email alerts
|

Rearing environment affects spatial learning in juvenile Chinook salmonOncorhynchus tshawytscha

Abstract: We tested the prediction that a complex physical rearing environment would enhance short-term spatial memory as assessed by learning ability in a spatial navigation task in juvenile Chinook salmon Oncorhynchus tshawytscha. We reared fish in two low-density treatments, where fish were either in bare fiberglass tanks (bare) or in tanks with physical structure (complex). We also tested conventionally reared high-density hatchery fish to compare with these other experimental treatments.Our reason for including thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Ion regulatory ability is key and can be influenced by stress that could affect behavior (Stewart et al 2016(Stewart et al , 2017. Visual isolation, as a consequence of structure in an environment, could also affect how fish respond to stressors and hence behavior (Cogliati et al 2019b). Other studies explored how physiology is involved in fish social behavior (Noakes and Leatherland 1977).…”
Section: Conducting Integrative Research That Bridges Behavior and Ph...mentioning
confidence: 99%
“…Ion regulatory ability is key and can be influenced by stress that could affect behavior (Stewart et al 2016(Stewart et al , 2017. Visual isolation, as a consequence of structure in an environment, could also affect how fish respond to stressors and hence behavior (Cogliati et al 2019b). Other studies explored how physiology is involved in fish social behavior (Noakes and Leatherland 1977).…”
Section: Conducting Integrative Research That Bridges Behavior and Ph...mentioning
confidence: 99%
“…Even though the assumption is common, there is surprisingly few studies demonstrating this, possibly because it is difficult to control for effects of previous experience when using wild individuals. However, several studies show cognitive differences between hatchery animals reared in different environments , Strand et al 2010, Salvanes et al 2013, Cogliati et al 2019, indicating that the rearing environment plays a part in cognition, at least in the short-term. Makino et al (2015) showed that learning ability of cultured striped knifejaws (Oplegnathus fasciatus) was inferior to wild conspecifics.…”
Section: Neurosensory Development and Cognitivementioning
confidence: 99%
“…Increased spatial learning in maze trials have been detected in rainbow trout, with effects increasing along with increased enrichment-exposure time (Ahlbeck- Bergendahl et al 2016). Positive effects on spatial learning have also been seen in Atlantic salmon (Salvanes et al 2013), but not in brown trout or chinook salmon , Cogliati et al 2019. This variation in effects seen in salmonids puts the generality of effects of enrichment into question, and it would be useful to further investigate what causes these differences (species-specificity, types of enrichment structures, experimental design, or other factors).…”
Section: Social Transfermentioning
confidence: 99%